2003
DOI: 10.1590/s0034-72992003000600010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da onda V da audiometria de tronco cerebral de crianças reprovadas na triagem auditiva neonatal

Abstract: Palavras-chave: triagem auditiva, audiometria de tronco cerebral , onda V. Key words: neonatal screening , brain auditory , V wave. Rev Bras Otorrinolaringol. V.69, n.6, 785-9, nov./dez. 2003 ORIGINAL ARTICLE ARTIGO ORIGINAL «««« ««««

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Many authors have reported that ABR results are influenced by the auditory maturation process and that their characteristics differ between premature and full-term babies [2,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported that ABR results are influenced by the auditory maturation process and that their characteristics differ between premature and full-term babies [2,[4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The prolongation of wave V latency can have different meanings, such as the maturation process of central auditory pathways or by peripheral conductive alteration, for instance. 30 All studies used in our review only included in their investigations full-term participants with normal hearing, who presented the bilateral presence of otoacoustic emissions and a type A tympanometry curve 10,16,25,27,31 and were free of risk factors, known for affecting hearing function. 15,26,28,29 Therefore, the risk factor studied that could affect hearing function was the SGA factor.…”
Section: Discussionmentioning
confidence: 99%